2019
DOI: 10.1016/j.rmcr.2019.02.021
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic effect of nintedanib on acute exacerbation of interstitial lung diseases

Abstract: Although the development of new antifibrotic agents (pirfenidone, nintedanib) has modified the disease progression of idiopathic pulmonary fibrosis (IPF), there is still no effective treatment for acute exacerbation of interstitial lung diseases (ILD) including IPF. We herein report a case of acute exacerbation of ILD (AE-ILD) treated only with nintedanib without any environmental changes and any other medications such as corticosteroid therapy, diuretic and anti-biotics, which resulted in the gradual improvem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…Usually, corticosteroid therapy is empirically used, with or without immunosuppressive agents and antibiotics. [205][206][207][208][209][210][211][213][214][215].…”
Section: Acute Exacerbation Of Ra-ildmentioning
confidence: 99%
See 1 more Smart Citation
“…Usually, corticosteroid therapy is empirically used, with or without immunosuppressive agents and antibiotics. [205][206][207][208][209][210][211][213][214][215].…”
Section: Acute Exacerbation Of Ra-ildmentioning
confidence: 99%
“…Finally, two patients with AE successfully treated with nintedanib without corticosteroids or immunosuppressants have been described [215,216].…”
Section: Acute Exacerbation Of Ra-ildmentioning
confidence: 99%
“…Other studies also identified a positive effect of a treatment with RTX with plasma exchange and intravenous immunoglobulin, polymyxin B-immobilized fiber column perfusion in patients diagnosed with IPF and intravenous thrombomodulin in CTD patients [159,164]. Recently, the effective use of Nintedanib in AE in IPF patients has been described in two patients [165,166], and, of note, in INPULSIS-2 trial there was a significant difference between the nintedanib and placebo groups in the time to the first acute exacerbation (hazard ratio, 0.38; 95% CI, 0.19 to 0.77; p = 0.005), even if the reliability of this result is still controversial [167,168].…”
Section: Pharmacological Treatmentmentioning
confidence: 93%
“…In two case studies an improvement in FVC was observed after initiation of nintedanib following an acute exacerbation [114,115]. There is a lack of real-world data on post-exacerbation survival in patients treated with nintedanib or pirfenidone.…”
Section: Use Of Nintedanib In Real-world Clinical Practicementioning
confidence: 99%